What is a good project manager? An Aristotelian perspective. Issue 2 (February 2015) - Bredillet, Christophe; Tywoniak, Stephane; Dwivedula, Ravikiran
Abstract The purpose of this paper is to take a critical look at the question "what is a competent project manager?" and bring some fresh added-value insights. This leads us to analyze the definitions, and assessment approaches of project manager competence. Three major standards as prescribed by PMI, IPMA, and GAPPS are considered for review from an attribute-based and performance-based approach and from a deontological and consequentialist ethics perspectives. Two fundamental tensions are identified: an ethical tension between the standards and the related competence assessment frameworks and a tension between attribute and performance-based approaches. Aristotelian ethical and practical philosophy is brought in to reconcile these differences. Considering ethics of character that rises beyond the normative deontological and consequentialist perspectives is suggested. Taking the mediating role of praxis and phrónêsis between theory and practice into consideration is advocated to resolve the tension between performance and attribute-based approaches to competence assessment.